2010
DOI: 10.1007/s12041-010-0052-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of genetic diversity using RAPD, SSR and cytochrome P450 gene based markers with respect to calcium content in finger millet (Eleusine coracana L. Gaertn.)

Abstract: Genetic relationships among 52 Eleusine coracana (finger millet) genotypes collected from different districts of Uttarakhand were investigated by using randomly amplified polymorphic DNA (RAPD), simple sequence repeat (SSR) and cytochrome P450 gene based markers. A total of 18 RAPD primers, 10 SSR primers, and 10 pairs of cytochrome P450 gene based markers, respectively, revealed 49.4%, 50.2% and 58.7% polymorphism in 52 genotypes of E. coracana. Mean polymorphic information content (PIC) for each of these mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 30 publications
5
39
3
Order By: Relevance
“…It was useful to analyze each of these components and their ramifications individually. Comparison of the diversity index calculated from the experimental data exhibited that EST-SSR was more polymorphic, which was in agreement with previous research in other plants (Milbourne et al, 1997;McGregor et al, 2000;Belaj et al, 2003;Panwar et al, 2010). However, TRAPs revealed high values of loci per assay unit, average number of polymorphic bands per assay unit, and high EMR, indicating that a large amount of genetic information could be detected using this marker, which was in keeping with the study by Alwala et al (2006) and Hu et al (2007).…”
Section: Discussionsupporting
confidence: 91%
“…It was useful to analyze each of these components and their ramifications individually. Comparison of the diversity index calculated from the experimental data exhibited that EST-SSR was more polymorphic, which was in agreement with previous research in other plants (Milbourne et al, 1997;McGregor et al, 2000;Belaj et al, 2003;Panwar et al, 2010). However, TRAPs revealed high values of loci per assay unit, average number of polymorphic bands per assay unit, and high EMR, indicating that a large amount of genetic information could be detected using this marker, which was in keeping with the study by Alwala et al (2006) and Hu et al (2007).…”
Section: Discussionsupporting
confidence: 91%
“…( [19]) attributed the variation among genotypes in minerals contents to differences in ecological conditions from which the finger millet genotypes originated. The results of this study also differ with findings of other workers who reported differences in Ca content among 36 finger millet genotypes ( [20]). Lack of variability in mineral content among the genotypes of this study occurred possibly because few genotypes were used or they originated from related genetic pool.…”
Section: Mineral Contentcontrasting
confidence: 99%
“…Therefore, they are widely used in genetic analysis (Berchowitz et al, 2001;Assogbadjo et al, 2010) as opposed to the RAPDs with low reproducibility (Powell et al, 1996). Microsatellites (or simple sequence repeats, SSRs) and especially chloroplast microsatellites (cpSSRs), have the power to reveal genetic diversity as well as phylogenetic relationships and hybridization between plant species (Wills et al, 2005;Panwar et al, 2010). Thus AFLPs and cpSSRs were used for these analyses.…”
Section: Genetic Diversitymentioning
confidence: 99%